PERFORMANCE OF LFAC SYSTEM FOR STEADY STATE - Amol D. Chate; Ashwini Pawar (International Journal of Innovations in Engineering Research and Technology, 2021)
HVAC power transmission using submarine power cables has limitation of charging current at nominal frequency. Therefore, HVDC power transmission technology has been established. However, a new intermediate technology of Low Frequency AC Transmission is established for transmission of power. This paper deals with the performance of a low-frequency ac (20Hz) transmission system for steady state. The LFAC system is interconnected with the 50Hz grid with a cycloconverter. The wind power from the offshore is in the form of dc, and is interconnected to the LFAC transmission line with a twelve-pulse thyristor inverter. The waveforms at the sending end and receiving end of the transmission line are plotted. The circuit model of LFAC system is simulated in MATLAB/SIMULINK.